2014
DOI: 10.12678/1089-313x.18.2.74
|View full text |Cite
|
Sign up to set email alerts
|

A Preseason Cardiorespiratory Profile of Dancers in Nine Professional Ballet and Modern Companies

Abstract: While studies have investigated the physical demands of dance in terms of cardiorespiratory fitness, there are no recent comparisons of cardiorespiratory response to exercise among professional dancers of different genres. Our purpose was to: 1. develop a cardiorespiratory profile of professional dancers; 2. investigate differences in peak and recovery heart rate (HR) between professional modern and ballet dancers using an accelerated 3-minute step test; 3. demonstrate the relationship between cardiorespirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 42 publications
2
35
1
Order By: Relevance
“…Previous studies had shown disparities in aerobic gains between styles of dance, so this study tested dancers who are trained in a variety of styles. 1,2,5 The mean estimated VO 2max of the dancers was higher than that of the athletes but the set of dancers had nearly three times the variance, which may reflect the wide variability in aerobic nature between different styles of dance. The mean estimated VO 2max of both dancers and traditional athletes was in the 70 th percentile for women as determined by the Aerobics Center Longitudinal Study .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies had shown disparities in aerobic gains between styles of dance, so this study tested dancers who are trained in a variety of styles. 1,2,5 The mean estimated VO 2max of the dancers was higher than that of the athletes but the set of dancers had nearly three times the variance, which may reflect the wide variability in aerobic nature between different styles of dance. The mean estimated VO 2max of both dancers and traditional athletes was in the 70 th percentile for women as determined by the Aerobics Center Longitudinal Study .…”
Section: Discussionmentioning
confidence: 93%
“…Studies that tested the aerobic fitness of professional contemporary and modern dancers compared to that of professional ballet dancers showed the contemporary and modern dancers to have higher maximal oxygen uptake, lower blood pressure, resting heart rates, and peak heart rate than ballet dancers. 2,5 The researchers hypothesized that the difference between genres is largely due to the tendency for modern dance numbers to be lengthier than ballet numbers, as well as to the decreased stigma against cross-training for modern dancers in comparison to ballet dancers. 5,6 Other studies examined muscular strength differences between dancers of different genres.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Professional dancers typically undergo high training loads and performance schedules that result in elevated physiological, biomechanical, and psychological stress [1,2]. In a typical 'work' day, reported rest periods are short and infrequent, and dancers may often dance for 40 hours per week through a combination of dance class, rehearsal, and performance [3,4]. Furthermore, rest-stress states in professional ballet dancers are akin to those observed in swimmers and footballers [5].…”
Section: Introductionmentioning
confidence: 99%